Interdependence of nursing staff work engagement, quality of workplace relationships and patient safety - Maze, Hilda (Organizacija (Kranj), 2023)
Background and Purpose: Quality within a healthcare system does not comprise only actions defined through certificates or required by law, standards and protocols; it is also defined by the well-being of healthcare workers on the one hand and patients on the other. The purpose paper is to analyse the link between the engagement of nurses and factors related to enhancing patient quality and safety. Methods: The research involved 206 nursing employees from Slovenia’s general hospitals. The questionnaire con-sists of four sections: employee engagement, the measure of self-efficacy, statements referring to various tools and methods that are used in nursing in daily work and that contribute to the quality of work, interpersonal relationships in the workplace between different professional groups within medical treatment, and attitude towards changes.Results: Compared to other professions, nursing employees showed an above-average level of engagement. Younger respondents were more engaged in their work, and their self-efficacy level was higher. The frequency of using tools intended to enhance the quality of nursing correlates statistically typically and positively with self-effica-cy, engagement and willingness to accept change. The analysed factors are interdependent. Engagement results from workplace interactions; employees who feel better in their workplace will be more oriented towards the future, be more open to innovation, and use various tools and approaches to enhance the work’s quality.Conclusion: Analysed concepts are closely connected and interdependent. The findings are essential for the suc-cessful and efficient management of hospitals and for ensuring patient quality and safety.
Keywords: delovna zavzetost; engagement; kakovost; nursing; pacienti; patient; quality; safety; samoučinkovitost; self-efficacy; varnost; zdravstvena nega